2010
DOI: 10.1088/0957-4484/21/48/485703
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion behaviour of nanostructured titanium substrates processed by high-pressure torsion

Abstract: Aseptic loosening induced by wear particles from artificial bearing materials is one of the main causes of malfunctioning in total hip replacements. With the increase in young and active patients, complications in revision surgeries and immense health care costs, there is considerable interest in wear-resistant materials that can endure longer in the harsh and corrosive body environment. Here, the tribological behaviour of nanostructured titanium substrates processed by high-pressure torsion (HPT) is investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…3a), revealing an increase on corrosion tendency. This indicates the fast After sliding, the OCP increased straight away to more noble values due to a re-growth of the passive film (repassivation) in the wear track [18,30,63]; however, it did not come back to the level before reciprocating sliding. This might indicate that the electrochemical state of the cpTi surface has been modified by the wear induced during mechanical solicitation, and therefore the newly formed passive film has dissimilar features when compared with the naturally one formed before mechanical loading [2].…”
Section: Electrochemical Behavior and Cof Measurementsmentioning
confidence: 96%
See 1 more Smart Citation
“…3a), revealing an increase on corrosion tendency. This indicates the fast After sliding, the OCP increased straight away to more noble values due to a re-growth of the passive film (repassivation) in the wear track [18,30,63]; however, it did not come back to the level before reciprocating sliding. This might indicate that the electrochemical state of the cpTi surface has been modified by the wear induced during mechanical solicitation, and therefore the newly formed passive film has dissimilar features when compared with the naturally one formed before mechanical loading [2].…”
Section: Electrochemical Behavior and Cof Measurementsmentioning
confidence: 96%
“…In accordance with Wang et al [29], nano-sized or ultrafine TiO 2 can cause genotoxicity and cytotoxicity in cultured human cells. The wear particles and corrosion products released from the metallic implant structures can induce to foreign body inflammatory responses with release of different cytokines, activation of macrophages, and consequent periprosthetic osteolysis and ultimately, the prosthesis failure [1,27,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…[99] In addition, a comparison of the tribocorrosion performances of coarse-grained and UFG Ti showed improved wear resistance in the UFG Ti with less plastic deformation under high contact pressures. [101] A recent experimental report described the use of ECAP to consolidate chips from the machining of Ti. [102] These experiments gave σ o = 182 MPa and k y = 11.…”
Section: The Hall-petch Relationship For Ufg Materialsmentioning
confidence: 99%
“…In 1991, Valiev et al reported the significance of grain refinement to the submicrometer and nanometer levels by HPT 3 . Over the last two decades, considerable interest has developed in processing materials through the application of HPT as a severe plastic deformation method not only for grain refinement [4][5][6] , but also for several other applications such as attainment of ultrahigh strength and high ductility [7][8][9] , attainment of high strength and high electrical conductivity 10 , achievement of high strength and high biocompatibility [11][12][13] , improvement of Tribocorrosion resistance 14 , improvement of wear resistance 15 , improvement of hydrogen storage capability [16][17][18] , achievement of photoluminescence effect 19 , controlling the allotropic phase transformations [19][20][21][22] , consolidation of machining chips 23,24 , consolidation of metallic powders [25][26][27] , production of supersaturated alloys 28,29 , and improvement of several other multifunctionalities [30][31][32] . Although most of these works are focused on HPT processing using bulk samples, consolidation of powders using HPT has recently received much attention [23][24][25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%